Response of Eggplant, Yard-Long Bean, and Kangkong on Polyethylene Mulched and Drip Irrigation System - Anas Dinurrohman Susila; Angga Agung Gumelar (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
<!– /* Font Definitions */ @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> Eggplant, yard long bean, and kangkong, were grown with polyethylene mulch with a drip irrigation system on Podzolic soil with low pH (4.5), low C-Organic (0.97%), very low total-N (0.17 %), low K content (0.15 me (100 g)-1), but had a high soil P2O5 concentration (13.7 ppm) to evaluate the best crop management practices under this soil condition. Combination of polyethylene mulch treatments (with and without), fertilizer (with and without), number of irrigation lines (0, 1, and 2 lines), and methods of fertilizer applications (preplant, split, and drip) were arranged in a Randomized Completely Block Design with four replications. The results showed that the use of mulch and fertilizer signiﬁ cantly increased yield of all crops. One line irrigation system also resulted in the best yield. Preplanting application of 100% P, 50% N and K in addition to 50% N and K applied 10 times weekly was the best methods to produce Eggplant, Yard Long Bean, Kangkong under polyethylene mulched and drip irrigation system. Keywords: Solanum melongena L, fertilization, fertigation, Ipomoea reptans L, micro-irrigation, polyethylene-mulched, Vigna unguilata L.